FPGA-Based Traffic Density Monitoring System - Teo, Valentine Teo Jin Lung; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2025)
The FPGA-based Traffic Density Monitoring System is designed to provide a real-time solution for monitoring and analyzing traffic conditions. This project aims to address the inefficiencies in traditional traffic management systems by utilizing the processing capabilities of Field-Programmable Gate Arrays (FPGAs). The primary objective is to enhance the efficiency of traffic flow by providing accurate and timely data on vehicle density. The methodology involves capturing live traffic data using advanced image sensors, which are then processed using FPGA hardware for real-time traffic density estimation. The system employs sophisticated image processing algorithms to detect and count vehicles within the monitored area, generating outputs that can assist traffic authorities in optimizing signal timings and mitigating congestion. Verilog programming and hardware optimization techniques are extensively utilized to ensure high-speed processing and accuracy in the system’s operations. The results demonstrate that the YOLOv8-based vehicle detection consistently achieved an accuracy of 95–98% under normal lighting conditions, while the FPGA finite state machine (FSM) was successfully validated in both simulation and hardware testing. The system maintained real-time responsiveness, with average end-to-end processing latency below 100 milliseconds even under high traffic loads. The system’s ability to operate in real-time makes it a viable and scalable solution for dynamic traffic management scenarios. Moreover, its cost-effective implementation offers the potential for widespread adoption in urban settings. In conclusion, this project highlights the transformative potential of FPGA technology in revolutionizing traffic monitoring systems. By offering a scalable, efficient, and cost-effective solution, it addresses modern urban challenges, paving the way for smarter and more sustainable cities.